Android-Based 'Tire-Math' Application Development: Integration of Business Mathematics in Receivables Management in MSMEs Tire Recycling to Support SDG 12 - Qurrotu A'yunin; Rani Darmayanti (Journal of Teaching and Learning Mathematics, 2026)
The issue of waste tires demands green entrepreneurial solutions to support the Sustainable Development Goals (SDG) 12 targets. However, MSMEs recycling tires in Surengrono face serious receivables management obstacles due to manual recording systems that have not implemented formal business mathematical concepts. This research aims to develop an Android-based "Tire-Math" application to integrate business mathematics into MSME receivables management. Using the Research and Development (R&D) method with a 4D (Define, Design, Develop, Disseminate) model, this research is limited to the Define and Design stages. The data collection technique is carried out through in-depth interviews with business owners and analysis of operational tasks. The data is analyzed descriptively to formulate features that are needed by the user. The research instruments include an interview guide and a wireframe validation sheet. The results of the design stage resulted in an initial prototype of an application that automates the calculation of receivables balances and provides a digital repayment reminder feature. The conclusion of the study shows that the integration of business mathematics competencies through digital platforms is a crucial innovation in strengthening the managerial capabilities and sustainability of MSME recycling tire entrepreneurship. Through this application, business actors can monitor cash flows more accurately, which has a direct impact on the economic stability of environmentally-based businesses.